A randomized controlled clinical trial to investigate the efficacy and safety of dexmedetomidine in treating postoperative acute pain - Yahui Liu; Jie Du; Yang Li; Qingxuan Zhang; Pu Li; Sha Li; Xiao Ma; Fupeng Xu (Saudi Journal of Anaesthesia)
Background: This study aims to investigate the efficacy and safety of dexmedetomidine in treating postoperative acute pain through a clinical randomized controlled trial. Methods: This study selected 165 patients who underwent general anesthesia surgeries at our hospital from October 2022 to May 2023 as research subjects. They were enrolled and randomly allocated to a control group (n = 73) and an experimental group (n = 74) based on a computer-generated random numbers table. Firstly, we compared the general clinical data before surgery. Secondly, we compared the pain degree, sedative degree, and vital signs at 6 time points (before surgery [T0], 1 h postoperatively [T1], 6 h postoperatively [T2], 12 h postoperatively [T3], 24 h postoperatively [T4], and 48 h postoperatively [T5]). Lastly, we compared the incidence of adverse reactions and comprehensive satisfaction degree for the two groups of patients after surgery. Results: The results showed that compared to the control group, the experimental group had lower VAS score, Ramsay score, mean arterial pressure (MAP), heart rate (HR), systolic blood pressure (SBP), and diastolic blood pressure (DBP) (P < 0.05), whereas blood oxygen saturation (SpO2) showed no change (P > 0.05). No difference was observed in the incidence of adverse reactions between the experimental and control groups (P > 0.05). The comprehensive satisfaction degree of patients in the experimental group was higher compared to the control group (P < 0.05). Conclusions: Dexmedetomidine could effectively manage the vital signs of patients with postoperative acute pain, improve treatment outcomes, alleviate pain, enhance sedation, ensure safety, and enhance comprehensive satisfaction.